Intrahepatic False Aneurysm: A Complication of Needle Biopsy - C. Wm Cole; John Lorimer; Lorraine B. Le Grand-Westfall (Canadian Journal of Gastroenterology)
Two months following intraoperative needle biopsy using a Tru-cut needle, the patient returned with a false aneurysm in the left lobe of the liver. Treatment consisted of complete excision of the lesion by left hepatic segmentectomy. The authors discuss therapeutic options for this unusual entity.